ETIKA PERDAMAIAN ISLAM DALAM WACANA GLOBAL - Ahmad Tajuddin Arafat (IAIN Tulungagung, 2017)
AbstractThis paper emphasizes on discussion about Islamic ethics and peace toward understanding the problem of globalization. By using content analysis approach, it’s founded that there are some points of Islamic ethics regarding with peace building concept in line with global discourse, which based on normative text and Islamic tradition. Islam, as a religion, stated that the ultimate purpose of Islam is submission to Allah as a God. But, Islam not only orients on the submission to God, but also emphasize deeply on the root of peaceful teachings and traditions. There are many texts from al-Qur’an and Hadith which already shared to us that Islam is well-known have promote the peaceful life and Muhammad selected as the Prophet of peace. In conclusion, Islam and peace cannot be separated in the daily life of Muslim. Keywords; Islamic ethics, peaceful Islam, globalization